한국어 용언활용에서 보이는 모음조화의 변이와 변화: 현장시와 실제시 연구 - 강희조 (언어학, 0(76), 2016)
This paper investigates the variation and change in the vowel harmony of verbal conjugation in Korean. By comparing the results of two judgment surveys, which were carried out in 2008 and in 2016, I show that not only the synchronic variation but the diachronic change is affected by morphophonological features such as regularity of stem, trigger vowel, and type of suffix. The innovation is faster in p-irregular stems, /a/-stems, and sentence-final suffixes than regular, /o/-stems, and other suffixes, respectively. With these results, I argue that the restructuring of stem forms and the perceptibility of morphemes play a crucial role in the acceleration or retardation of change. In addition, this study also shows that variation does not always result from the instability of change. KCI Citation Count: 1